PENGARUH KOMPETENSI PEDAGOGIK DAN MOTIVASI TERHADAP HASIL BELAJAR SISWA KELAS IX PADA MATA PELAJARAN IPS DI SMP KATOLIK ST. THERESIA KUPANG - See, Siprianus (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to reveal the influence of pedagogical competence and student motivation on the learning outcomes of class IX students in social studies subjects at St. Catholic Middle School. Theresia Kupang, both partially and simultaneously. This research is quantitative research. The research subjects were 93 class IX students of Sta Catholic Middle School. Theresia Kupang. Data were analyzed using Regression Statistics. The results of the Regression Analysis show that the effective contribution of the Pedagogical Competency variable to the learning outcomes of class IX students in social studies subjects at SMPK St. Theresia Kupang is Rsquare = 0.370 x 100% = 37%. (2) Coefficient of determination or effective contribution of the Student Motivation variable to Class IX Student Learning Outcomes in Social Sciences subjects at SMPK St. Theresia Kupang is Rsquare = 0.400 x 100% = 40%. (3) Meanwhile, the coefficient of determination or effective contribution of Gogic Competence and Student Motivation together on Class IX Student Learning Outcomes in Social Sciences subjects at SMPK St. Theresia Kupang is Rsquare = 0.485 x 100% = 48.5%. Thus it can be concluded that both partially and simultaneously pedagogical competence and learning motivation have a positive and significant effect on the learning outcomes of class IX students in social studies subjects at SMPS Sta. Theresia Kupang.